Pengaruh Terapi Akupresur terhadap Nyeri Dismenore pada Siswa SMA Muhammadiyah 7 Surabaya - Mia Isnayati Deby; A’im Matun Nahiroh; Irma Maya Puspita (Rena Cipta Mandiri, 2025)
Dysmenorrhea pain is a cramp in the lower abdomen that occurs before menstruation or during menstruation. WHO (2017) said that 50% of women in every country experience dysmenorrhea. Treatment of dysmenorrhea consists of pharmacological and non-pharmacological. One of the non-pharmacological treatments is acupressure therapy. This study aims to determine the effect of acupressure therapy on dysmenorrhea pain in female students of SMA Muhammadiyah 7 Surabaya. The type of research used is quantitative, Quasi Experiment One Group Prepost-test research design. The study was conducted in January 2023 at SMA Muhammadiyah 7 Surabaya. The sampling technique used cluster sampling, with a sample size of 29 female students. The results of the study showed that before being given acupressure therapy, the majority of female students experienced moderate dysmenorrhea pain as many as 20 female students (69%) and a minority of severe pain as many as 5 female students (17.2%), after being given acupressure therapy, the pain scale experienced became mild as many as 26 female students (89.7%) and moderate pain as many as 3 female students (10.3%), the results of the data analysis test using paired sample T-test obtained a p-value of 0.000 <0.05, meaning that there is an effect of acupressure therapy on dysmenorrhea pain. Pressing the acupressure points at the taichong point (LV 3) and the sanyinjiao point (SP6) can reduce the sensation of dysmenorrhea pain, by increasing the hormone endorphin. The hormone endorphin is a hormone that can bring a sense of relaxation to the body naturally, which can release pain receptors to the brain.